Microreactor production by PolyJet Matrix 3D-printing technology : hydrodynamic characterization - Šercer, Mladen (Array, 2019)
This work investigates the methodology of producing a 3D-printed microreactor from the acrylic resin by PolyJet Matrix process. The PolyJet Matrix technology employs different materials or their combinations to generate 3D-printed structures, from small ones to complex geometries, with different material properties. Experimental and numerical methods served for the evaluation of the geometry and production of the microreactor and its hydrodynamic characterization. The operational limits of the single-phase flow in the microchannels, further improvements and possible applications of the microreactor were assessed based on the hydrodynamic characterization.